Clients, mandataires et partenaires silencieux : Configurations du conflit américano-soviétique en Asie du Sud-Est - Van Der Kroef, Justus (Études internationales, 1982)
In the Southeast Asian area modalities of political dependence have developed which involve the distinctive typology of clients, silent partners, and proxies. These modalities govern the relationship between the Socialist Republic of Vietnam, Laos, and the People's Republic of Kampuchea. They also are operative in the international interaction between the members of the Association of Southeast Asian nations (Asean) and the Western major powers. A set of strategic cooperative arrangements, as well as direct military assistance between Asean, the Commonwealth and the U.S., has its counterpart in similar relations between the U.S.S.R. and the Hanoi dominated lndo-China alliance. As a result, the U.S.-Soviet confrontation in Southeast Asia is expressed politically and strategically primarily through the proxy relationships with the lndo-China states and key Asean members respectively. In turn, there are strong undercurrents in Asean seeking an accommodation with Hanoi, in order to minimize the conflict potential in the region generated by opposing U.S. and Soviet strategic interests. Particularly the relatively warming relationship between the U.S. and People's China has strengthened the Asean fears of China s long-term intentions in the region. An independent Vietnam, free from its proxy-client status toward the Soviet Union, could act as a buffer between China and the Southeast Asian region. Since Hanoi, if only for long-standing nationalistic reasons, wishes to be free from its currently necessary dependence on Moscow, Asean's accommodationist interests may well meet with appreciation in Hanoi in the future. This would tend to lessen the effect of the American-Soviet confrontation in the area.